Rethinking Statehood in Palestine Self-Determination and Decolonization Beyond Partition - Farsakh, Leila H. (University of California Press, 2021)
The quest for an inclusive and independent state has been at the center of the Palestinian national struggle for a very long time. This book critically explores the meaning of Palestinian statehood and the challenges that face alternative models to it. Giving prominence to a young set of diverse Palestinian scholars, this groundbreaking book shows how notions of citizenship, sovereignty, and nationhood are being rethought within the broader context of decolonization. Bringing forth critical and multifaceted engagements with what modern Palestinian self-determination entails, Rethinking Statehood sets the terms of debate for the future of Palestine beyond partition.